A study on financial impacts of labour turnover in International Trade Department In Scope International (M) Sdn Bhd / Mohd Fahmi Izzuddin Ishak - Ishak, Mohd Fahmi Izzuddin (Faculty of Business and Management, 2010)
Labour turnover is one of the major losses to all types of businesses. The rate will not going to decrease if there is no actions regarding on hiring new employees, giving full training and so on. In Scope International, as a subsidiary of Standard Chartered Bank, they believed that the issue comes from this matter should be taking seriously as the operations of the company will effect a lot if the problem cannot be solved properly and timely. For International Trade department, high labour turnover has costs many things. The first impact is the cost of employee leaving, the cost of training, the cost of hiring and also the operation losses. According to the manager of the department, the costs have been estimated or prepared earlier every beginning of the year but the losses from the labour turnover still happen or cannot be avoided. This study is an attempt to analyze about the financial impacts of labour turnover in International Trade department of Scope International (M) Sdn Bhd and how much the costs that the company already have to face and do some reactions. The method that the researcher has used was interviewing. By interview, the researcher has found out the total costs of the labour turnover and has given some recommendations towards it in terms of time, money, rewards and so on. From this research, it will give the overview of the financial impacts of labour turnover and also information of how the costs affect the company and also the bank as a whole.